Recent growth in occurrences of Acrida ungarica (Orthoptera: Acrididae) at the northern margin of the species range: Is it the result of global warming? - Zoltán KENYERES; Norbert BAUER; Thomas ZUNA-KRATKY; Máté MAGYARI; Josip SKEJO; Anton KRIŠTÍN (European Journal of Entomology, 2023)
The number of records of Acrida ungarica in novel habitats and in places where the species was considered extinct, has markedly increased in recent years. We hypothesized that the newly revealed occurrences, on the northern margin of the species range, were not due to an increase in survey effort, but rather a result of the warming climate in the Carpathian Basin. We studied the occurrence data of Acrida ungarica and the intensity of Orthoptera surveys over the period of 2002-2022 in 1,840 6 × 5.5 km grid cells of the Central European Flora Mapping System. As background variables, we included macroclimatic data and the vegetation cover of the main potential habitats. The number of grid cells containing A. ungarica was significantly higher than the corresponding increase in cells surveyed for orthopterans and the presence of sand and salt steppe habitats, respectively. Furthermore, from 2012 to 2022, significant increasing trends were revealed in effective heat summation above 10°C in the summer months. That the increase in the known distribution of A. ungarica is unrelated to the rise in survey intensity indicates that the species distribution seems to be increasing, making it one of the winners from global warming. At the same time, regional rising levels of disturbance (highway networks, large fallow areas) can contribute to the successful horizontal expansion of a species related to open habitats and this species tolerance of disturbance.